Immunological mechanisms contributing to the double burden of diabetes and intracellular bacterial infections. Issue 2 (February 2015) - Hodgson, Kelly; Morris, Jodie; Bridson, Tahnee; Govan, Brenda; Rush, Catherine; Ketheesan, Natkunam
Summary Diabetes has been recognized as an important risk factor for a variety of intracellular bacterial infections, but research into the dysregulated immune mechanisms contributing to the impaired host–pathogen interactions is in its infancy. Diabetes is characterized by a chronic state of low‐grade inflammation due to activation of pro‐inflammatory mediators and increased formation of advanced glycation end products. Increased oxidative stress also exacerbates the chronic inflammatory processes observed in diabetes. The reduced phagocytic and antibacterial activity of neutrophils and macrophages provides an intracellular niche for the pathogen to replicate. Phagocytic and antibacterial dysfunction may be mediated directly through altered glucose metabolism and oxidative stress. Furthermore, impaired activation of natural killer cells contributes to decreased levels of interferon‐γ, required for promoting macrophage antibacterial mechanisms. Together with impaired dendritic cell function, this impedes timely activation of adaptive immune responses. Increased intracellular oxidation of antigen‐presenting cells in individuals with diabetes alters the cytokine profile generated and the subsequent balance of T‐cell immunity. The establishment of acute intracellular bacterial infections in the diabetic host is associated with impaired T‐cell‐mediated immune responses. Concomitant to the greater intracellular bacterial burden and potential cumulative effect of chronic inflammatory processes, late hyper‐inflammatory cytokine responses are often observed in individuals with diabetes, contributing to systemic pathology. The convergence of intracellular bacterial infections and diabetes poses new challenges for immunologists, providing the impetus for multidisciplinary research.